2012
DOI: 10.1038/ng.2446
|View full text |Cite
|
Sign up to set email alerts
|

De novo gene mutations highlight patterns of genetic and neural complexity in schizophrenia

Abstract: To evaluate evidence for de novo etiologies in schizophrenia, we sequenced at high coverage the exomes of families recruited from two populations with distinct demographic structure and history. We sequenced a total of 795 exomes from 231 parent-proband trios enriched for sporadic schizophrenia cases, as well as 34 unaffected trios. We observed in cases an excess of non-synonymous single nucleotide variants as well as a higher prevalence of gene-disruptive de novo mutations. We found four genes (LAMA2, DPYD, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
402
3
20

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(443 citation statements)
references
References 35 publications
18
402
3
20
Order By: Relevance
“…This hypothesis did not receive much attention in genetic studies until recently, when high-throughput DNA sequencing of SCZ families provided direct evidence that affected offspring have excess DNMs across the genome [72,73] . Further studies of DNMs in individual genes [74,75] , a particular set of genes [76,77] , or the exome [78][79][80] , also provided evidence that DNMs are enriched in SCZ patients. Direct measurement also indicates that SCZ patients have a higher mutation rate [76] .…”
Section: De Novo Mutations In Sczmentioning
confidence: 95%
See 2 more Smart Citations
“…This hypothesis did not receive much attention in genetic studies until recently, when high-throughput DNA sequencing of SCZ families provided direct evidence that affected offspring have excess DNMs across the genome [72,73] . Further studies of DNMs in individual genes [74,75] , a particular set of genes [76,77] , or the exome [78][79][80] , also provided evidence that DNMs are enriched in SCZ patients. Direct measurement also indicates that SCZ patients have a higher mutation rate [76] .…”
Section: De Novo Mutations In Sczmentioning
confidence: 95%
“…It should be pointed out that DNMs can be CNVs [48,81] , Detailed analyses of DNMs in affected offspring reveal an excess of missense and disrupting mutations in proteincoding sequences, especially those involved in synaptic functions [77,79] . While most DNMs are unique events, some are recurrent [79] .…”
Section: De Novo Mutations In Sczmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the genetic homogeneity, the Afrikaners are valuable for genetic studies because they present a close-knit family structure and offer the potential to perform detailed genealogical analysis, which affords reliable discrimination of familial and non-familial (sporadic) forms of the disease (Xu et al, 2012). We identified and extracted the sporadic cohort (i.e.…”
Section: Subject Recruitmentmentioning
confidence: 99%
“…Research investigations using Genome Wide Association Study (GWAS) (Network and Pathway Analysis Subgroup of the Psychiatric Genomics Consortium, 2015; Wood, 2013), exome‐based sequencing (Girard et al, 2011; Iossifov et al, 2012; O'Roak et al, 2011; Vissers et al, 2010; Xu et al, 2012), and whole genome sequencing (Kong et al, 2012) techniques have revealed several candidate genes that are associated with common neuropsychiatric disorders such as Autism Spectrum Disorder (ASD), intellectual disability, and schizophrenia. However, in the case of rare disorders, understanding the genetic origins and progressions of disorders—one of the key objectives of Precision Medicine research (Collins & Varmus, 2015; Kohane, 2015; Kohane, Churchill, & Murphy, 2012)—is hindered by small patient population size, the consequent paucity of patient data, and the lack of robust phenotyping protocols (Baynam et al, 2015; Delude, 2015; Robinson, Mungall, & Haendel, 2015).…”
Section: Introductionmentioning
confidence: 99%